Seed, sprout, pumpkin, pie - Esbaum, Jill. (Washington, D.C. : National Geographic, 2009)
Discusses how pumpkins grow, the different varieties of pumpkins, and the many ways people use them.
OSLIS\Gale Nat Geo eBooks(2/2/23).
"National Geographic kids."
Description based on print version record.
Keywords: Pumpkin -- Juvenile literature; Pumpkin; Electronic books- OSLIS; Electronic books